PHOTOCATALYST ACTIVITY OF MgO FROM BANGKALAN DOLOMITE - Rahmawati, Isna; Rohmawati, Lydia (Indonesian Physical Review, 2022)
In the industrial sector, water pollution due to dye waste needs special attention because it can harm humans and the environment. A waste-absorbing material with good photocatalytic properties is required to overcome this problem. The photocatalytic properties are owned by metal oxide materials, one of which is Magnesium Oxide (MgO) material. This study aims to analyze the activity level of MgO photocatalytic from Bangkalan dolomite. MgO synthesis was carried out by the leaching method, where UV-Vis characterized the results to determine the photocatalytic ability of MgO against methylene blue (MB). In this characterization, various treatments (sunlight, UV light, and darkroom conditions) were carried out with radiation times of 180, 240, and 300 minutes. The results of the UV-Vis spectrum analysis showed that MgO had a band gap of 4.01 eV. The degradation efficiency of photocatalytic obtained optimal under sunlight, UV light, and in a dark room with a radiation time of 300 minutes at 82%, 42%, and 34%. Thus, the synthesis of MgO in sunlight showed good photocatalytic activity in reducing MB dye to use for processing waste from the dye industry.